THE CULTURE OF SHAME: BETWEEN THE CHALLENGES AND THREATS OF SOCIAL MEDIA IN THE ERA OF DIGITALIZATION (THE CONCEPT OF ISLAMIC FAMILY LAW) - Asmita, Sri; Sarip, Muhammad (Fakultas Syariah UIN Sultan Maulana Hasanuddin Banten, 2023)
The era of digital transformation is an era of disruption that changes all aspects of human life, which is marked by the shift of human ideology to social conditions that occur in society. This is growing along with technological advances that are much favored by millennial people today, especially in social media. This paper is based on the argument that the shifting culture of shame in Indonesian society in social media, so that it becomes a challenge and threat for users. This study uses a library research approach by obtaining data sourced from online and offline, thus providing an objective picture of how the concept of shame in Islamic family law between the challenges and threats of social media in the era of digital transformation. The study in this study is qualitative descriptive, by obtaining evidence through Google engines such as YouTube, Instagram, Twitter, and other social media. This paper shows that social media in an unwise way causes a shift in understanding towards the use of technology, thus distorting the concept of shame in Islamic family law. The number of widows and widowers indulges in shame during marriage on social media, as well as between mother and child, so that there is no more privacy in every daily activity, this is a big challenge for Islamic family law in placing the concept of shame to anticipate disharmony in the household.